“I Have All the Time in the World”: Bernadette Mayer’s Being in Time - Amy Moorman Robbins (Humanities, 2025)
This essay argues that several of Bernadette Mayer’s major works foreground and develop experiences of subjective time as moments of resistance to the standardizing force of objective clock and calendric time that governs daily material existence. Basing my argument on a framework for subjective time developed in the field of linguistics, I show how Mayer’s play with duration, temporal recursiveness, and moments of stopped time in works including Memory, Midwinter Day, Works and Days, and Milkweed Smithereens function as subversions of the normative material every day, and I argue that throughout her work Mayer is preoccupied with not merely representing time, its content, and its passage, but rather with gaining mastery over objective time and subverting its authority altogether. This essay joins the scant research on time and temporality in Mayer’s work and offers an invitation to further study of subjective time as a mode of resistance in contemporary poetry.